Signal Analysis on Strings for Immune-Type Pattern Recognition. Issue 1 (2004) - Atreas, Nikolaos D.; Karanikas, Costas; Polychronidou, Persefoni
Abstract : We use wavelet-type discrete transforms for signal analysis on strings of finite length. We apply these transforms for edge and hidden Markov process detection. We also present new approaches for string matching and for measures of the diversity of chaotic strings.